2015
DOI: 10.1186/s12974-015-0335-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 is increased in multiple sclerosis patients and targets astrocytes

Abstract: BackgroundIncreasing evidences link T helper 17 (Th17) cells with multiple sclerosis (MS). In this context, interleukin-22 (IL-22), a Th17-linked cytokine, has been implicated in blood brain barrier breakdown and lymphocyte infiltration. Furthermore, polymorphism between MS patients and controls has been recently described in the gene coding for IL-22 binding protein (IL-22BP). Here, we aimed to better characterize IL-22 in the context of MS.MethodsIL-22 and IL-22BP expressions were assessed by ELISA and qPCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 62 publications
3
82
0
Order By: Relevance
“…In a similar study, microbial amyloid was shown to be able to activate T-lymphocytes and induce the production of pro-inflammatory interleukins IL-17A and IL-22 (Nishimori et al, 2012). These cytokines are able to penetrate the blood-brain barrier and cause the production of reactive oxygen species, activation of the TLR2/1 and NFÎB signaling pathways in microglia and astrocytes, which is directly related to neuroinflammation and neurodegeneration (Perriard et al, 2015;Sun et al, 2015;Zhan et al, 2018). Besides Chen et al demonstrated that oral contamination of old rats (previously subjected to antibiotic treatment) with wild E. coli strain, capable of producing the functional curli peptide, led to an increase in brain tissue microgliosis and astrogliosis and increased expression of TLR2, IL6, and TNF (Chen et al, 2016a).…”
Section: Possible Mechanisms Underlying the Effect Of Gut Microbiomementioning
confidence: 88%
“…In a similar study, microbial amyloid was shown to be able to activate T-lymphocytes and induce the production of pro-inflammatory interleukins IL-17A and IL-22 (Nishimori et al, 2012). These cytokines are able to penetrate the blood-brain barrier and cause the production of reactive oxygen species, activation of the TLR2/1 and NFÎB signaling pathways in microglia and astrocytes, which is directly related to neuroinflammation and neurodegeneration (Perriard et al, 2015;Sun et al, 2015;Zhan et al, 2018). Besides Chen et al demonstrated that oral contamination of old rats (previously subjected to antibiotic treatment) with wild E. coli strain, capable of producing the functional curli peptide, led to an increase in brain tissue microgliosis and astrogliosis and increased expression of TLR2, IL6, and TNF (Chen et al, 2016a).…”
Section: Possible Mechanisms Underlying the Effect Of Gut Microbiomementioning
confidence: 88%
“…Whether IL-22 can directly affect glial cells and regulate cell function is not entirely clear. IL-22 receptor was detected in human astrocytes of both healthy controls and multiple sclerosis patients, and IL-22 treatment reduced TNF-α-induced apoptosis of astrocytes [16]. In addition, exogenous IL-22 also promoted the proliferation of human glial cells accompanied by an anti-apoptotic effect [50].…”
Section: Discussionmentioning
confidence: 99%
“…In a lethal West Nile virus (WNV) encephalitis mouse model, IL-22 de ciency resulted in reduced viral load, decreased in ammatory in ltration and alleviated tissue pathology [15]. In addition, IL-22 was increased in multiple sclerosis patients [16] and could disrupt blood-brain barrier (BBB) tight junctions [17]. These studies suggest that IL-22 may play a detrimental role in the central nervous system (CNS) during viral infection.…”
mentioning
confidence: 99%
“…The serum IL-22 level is increased during relapse in relapsing-remitting MS patients compared to healthy controls, in patients with remission and those with primary progressive MS (ref. 21 ). Similarly, an increase in CD4 + IL-22 + percentage in peripheral blood was observed by N. Muls et al during relapse when compared to remission 22 .…”
Section: Il-22mentioning
confidence: 99%